2017
DOI: 10.1016/j.foodchem.2017.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Volatile profile in the accurate labelling of monofloral honey. The case of lavender and thyme honey

Abstract: The proliferation of hybrid plant varieties without pollen, such as lavender, has complicated the classification of specific types of honey. This study evaluated the correlation between the proclaimed type of monofloral honey (lavender or thyme) as appears on the label with the actual percentage of pollen. In addition, physicochemical parameters, colour, olfacto-gustatory profile, and volatile compounds were tested. All of the samples labelled as lavender were wrongly classified according to the usual commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
1
25
0
2
Order By: Relevance
“…Although other Lavandula species are not mentioned in the present studies, they may also contribute to the production of lavender honey, namely Lavandula pedunculata and Lavandula luisieri ("Rozeira" in Portuguese)-both very common in Portugal [109,110]. Some authors (Table 11) have pointed out linear aldehydes like hexanal and heptanal as characteristic of Lavandula honeys [49,52,79,98,111,112], although other studies showed marked differences in volatile profiles between the four monofloral types of this honey [41,79,99]. For instance, Lavandula angustifolia honey has a dominance of floral and honey-like smelling compounds like phenylacetaldehyde, phenylethanol, and β-damascenone [41], whereas Lavandula latifolia honey could be distinguished by the presence of 3,7-dimethyl-1,5,7-octatrien-3-ol and 3,5,5-trimethyl-2-cyclohexen-1-one, as well a high amount of 2,3-butanediol [99].…”
Section: Lavender Honeymentioning
confidence: 75%
See 2 more Smart Citations
“…Although other Lavandula species are not mentioned in the present studies, they may also contribute to the production of lavender honey, namely Lavandula pedunculata and Lavandula luisieri ("Rozeira" in Portuguese)-both very common in Portugal [109,110]. Some authors (Table 11) have pointed out linear aldehydes like hexanal and heptanal as characteristic of Lavandula honeys [49,52,79,98,111,112], although other studies showed marked differences in volatile profiles between the four monofloral types of this honey [41,79,99]. For instance, Lavandula angustifolia honey has a dominance of floral and honey-like smelling compounds like phenylacetaldehyde, phenylethanol, and β-damascenone [41], whereas Lavandula latifolia honey could be distinguished by the presence of 3,7-dimethyl-1,5,7-octatrien-3-ol and 3,5,5-trimethyl-2-cyclohexen-1-one, as well a high amount of 2,3-butanediol [99].…”
Section: Lavender Honeymentioning
confidence: 75%
“…Regarding lavandin honey, the mean contents, including lactones, namely γ-butyrolactone, pantolactone and γ-nonalactone, are higher than those in other lavender honeys [113]. Methyl alcohols were also abundant in lavender honey, especially 2-methyl-3-buten-2-ol [49,99,101], 3-methyl-2-buten-1-ol [98,99,112], and 2-methyl-2-buten-1-ol [49,97,99]. Based on the analysed data (Table 11), it was not possible to identify reliable markers that could differentiate the volatile profile of the four lavender honey types.…”
Section: Lavender Honeymentioning
confidence: 85%
See 1 more Smart Citation
“…Physicochemical parameters (color, moisture, acidity) can vary widely in different types of honey and this contributes, to a certain extent, to their organoleptic characteristics. This is the reason why chromatographic techniques are more eloquent in the classification of honey and special attention should be paid to identifying certain specific minor components [20]. In addition to the classical techniques used to authenticate honey, the use of DNA-based methods for pollen identification has also spread.…”
mentioning
confidence: 99%
“…These compounds have been found to discriminate among different type of honeys, such as thyme and lavender honey. 17 Acetic acid was the third highest concentrated volatile followed by methanol and ethanol in the honeys, except for chestnut honeys from Yalova region and lavender (Table 3). Acetic acid is formed through degradation of alcohols and produce acidic aroma in honey.…”
Section: Resultsmentioning
confidence: 98%